ANALISIS PENGARUH PELAKSANAAN SUPPLY CHAIN DAN LOGISTIK TERHADAP KINERJA PERUSAHAAN MANUFAKTUR - Yolanda M. Siagian (Universitas Trisakti, 2007)
The emergence of the extended manufacturing enterprise, a globalIy dispersed collection of strategically aligned organizations, has bought new attention to how to coordinate the flow of information and materials across their supply chain. This paper explores and develops the concept of enterprise logistics. Specifically, this paper examines the fit between organization's enterprise logistics integration capabilities and its supply chain structure. Using a configuration approach, we test whether globally dispersed network organizations that adopt enterprise logistics practices that are able to achieve higher levels of organizational performance. Result, indicate that enterprise logistics is a necessary tool for a pure network structure, a high level of enterprise logistics integration alone does not guarantee improved organizational performanceKeywords : Information & materials, enterprice logistic supply change, organizational performance